GRANADA (GERAKAN ANTI NIKAH MUDA) ; EDUKASI DAN SOSIALISASI DAMPAK PERNIKAHAN DINI SEBAGAI UPAYA PENDEWAWAAN USIA PERKAWINAN PADA REMAJA DI SMPN 3 PELAYANGAN KOTA JAMBI - Sari, Rumita Ena; Siregar, Sri Astuti; Ibnu, Ismi Nurwaqiah (Prodi Ilmu Kesehatan Masyarakat, FKIK Universitas Jambi, 2024)
The impact of marriages that are not old enough results in high divorce rates due to various reasons. Starting from financial problems, because they are not yet established enough to support the family, emotional and psychological problems, to problems with the roles of husband and wife not being optimal. Based on research conducted by the author in 2022 in 13 sub-districts spread across the working areas of the Olak Kemang, Tahtul Yaman, Koni and Putri Ayu Community Health Centers, Jambi City, 58% of women under 20 years of age who have toddler children whose growth and development does not match their age range The aim of this service is to provide education and outreach about the impact of early marriage. The implementation method in this research is to provide education and socialize the impact of early marriage to the community groups being trained. As many as 49% of students have low knowledge. As many as 60% of students have high knowledge after being educated about the anti-young marriage movement in an effort to increase the age of marriage. The results of descriptive statistical tests are the average and standard deviation of knowledge between the first measurement (pretest) and the second measurement (posttest). The average knowledge in the first measurement was 6.3800 with a standard deviation of 1.73. In the second measurement, the average knowledge was found to be 11.5200 with a standard deviation of 0.64. The paired T test is reported in the second table, it can be seen that the mean value of the difference between the first and second measurements is 0.514 with a standard deviation of 1.79. This difference was tested with a paired T test producing a p value which can be seen in the